Application of human pluripotent stem cells and pluripotent stem cell-derived cellular models for assessing drug toxicity. (2nd January 2019) - Apáti, Ágota; Varga, Nóra; Berecz, Tünde; Erdei, Zsuzsa; Homolya, László; Sarkadi, Balázs
ABSTRACT: Introduction : Human pluripotent stem cells (hPSCs) are capable of differentiating into all types of cells in the body and so provide suitable toxicology screening systems even for hard-to-obtain human tissues. Since hPSCs can also be generated from differentiated cells and current gene editing technologies allow targeted genome modifications, hPSCs can be applied for drug toxicity screening both in normal and disease-specific models. Targeted hPSC differentiation is still a challenge but cardiac, neuronal or liver cells, and complex cellular models are already available for practical applications. Areas covered : The authors review new gene-editing and cell-biology technologies to generate sensitive toxicity screening systems based on hPSCs. Then the authors present the use of undifferentiated hPSCs for examining embryonic toxicity and discuss drug screening possibilities in hPSC-derived models. The authors focus on the application of human cardiomyocytes, hepatocytes, and neural cultures in toxicity testing, and discuss the recent possibilities for drug screening in a 'body-on-a-chip' model system. Expert opinion : hPSCs and their genetically engineered derivatives provide new possibilities to investigate drug toxicity in human tissues. The key issues in this regard are still the selection and generation of proper model systems, and the interpretation of the results in understanding in vivo drug effects.